Value co-creation in the beverage and food industry - Tardivo, Giuseppe; Thrassou, Alkis; Viassone, Milena; Serravalle, Francesca (British food journal (1966), 2017)
Purpose The purpose of this paper is to define and describe how consumers may constitute an integral part of small and medium enterprises’ (SMEs) value co-creation process in the food and beverage (F&B) industry, and to provide practicable implementation recommendations to firms in the Piedmont region that are important and prominent in this sector. Design/methodology/approach The research methodology rests on a multiple case study design, applied to three F&B Piedmont SMEs that produce beer, water and starters: Baladin, Lurisia and Galfré. Findings Results show an increasing awareness by firms of the important role played by customers in value co-creation, though limited to specific roles in the case of SMEs. Research limitations/implications The research is limited by its exploratory nature, though the findings and conclusions drawn provide a solid foundation for further development and testing on the subject. Practical implications The case studies’ results allow the reader to understand the importance of the increasing awareness of the role played by customers in value co-creation, especially on the WWB, where costs are minimizing. Originality/value The research’s value stems from fact that there are few existing studies on the ways to engage customers in value co-creation. Moreover, these studies, contrary to the present research, are largely theoretical and either have no direct applicability or are limited to a single case.